The Importance of Curriculum Components in PAI Learning - Erihadiana, Mohamad; Zakiyyah, Qothrun Nada (Jurnal Ar Ro'is Mandalika (Armada), 2022)
The curriculum is the core of the education system and plays an important role in developing and managing learning programs in an educational institution. The method used in this research is library research. There are 4 elements to the curriculum components, namely objectives, content/material, strategies/methods, and evaluation. In the PAI learning curriculum there are curriculum components related to Islam which aim to create students who are devoted to Allah SWT and have noble morals. From the description above, it can be concluded that the curriculum components in PAI learning are very important. Because the four components discussed above are interrelated.